Mechanical small bowel obstruction as a complication of pregnancy - Adamczyk-Gruszka, Olga K.; Lewandowska-Andruszuk, Izabela J.; Głuszek, Stanisław; Gruszka, Jakub A. (Medical Studies/Studia Medyczne, 2015)
Abdominal pain is a common complaint in pregnancy. Intestinal obstruction reported in pregnancy varies, ranging from 1 in 1500 to 1 in 66431 pregnancies. Unfortunately, “dormant alertness” can lead to delayed surgical intervention, which in turn can increase the risk of complications that pose a threat to the mother as well as her foetus. The paper presents a case of a 23-year-old pregnant woman diagnosed with mechanical small bowel obstruction in 27 hbd, which required surgical emergency operation. The necrotic loop of the small intestine was resected. Despite tocolysis, which was necessary on the second day following the surgery, the patient was discharged home in good condition, with her pregnancy intact.